Racism in the Hands of an Angry God: How Image of God Impacts Cultural Racism in Relation to Police Treatment of African Americans - Lauve-Moon, Tim A. (Journal for the scientific study of religion, 2023)
Previous research suggests an angry God image is a narrative schema predicting support for more punitive forms of criminal justice. However, this research has not explored the possibility that racialization may impact one's God image. We perform logistic regression on Wave V of the Baylor Religion Survey to examine the correlation between an angry God image and the belief that police shoot Blacks more often because Blacks are more violent than Whites (a context-specific form of cultural racism). Engaging critical insights from intersectionality theory, we also interact angry God image with both racialized identity and racialized religious tradition. Results suggest that the angry God schema is associated with this form of cultural racism for White people generally as well as White Evangelicals, yet for Black Protestants, belief in an angry God is associated with resistance against this type of cultural racism.